Monument dedicated to the Jewish volunteers who fell in Spain 1936-1939, unveiled by President Chaim Herzog in 1990
Monument dedicated to the Jewish volunteers who fell in Spain 1936-1939, unveiled by President Chaim Herzog in 1990.